Physical activity of community-dwelling adults with traumatic spinal cord injuries in the Cape Metropole. - Gabriels, Aeysha; Ismail, Toughieda; Bezuidenhout, Lucian; Joseph, Conran (South African Journal of Physiotherapy, 2025)
Background: Physical activity (PA) is an important indicator for disease prevention in adults with spinal cord injuries (SCIs). Regular PA can improve functioning, community reintegration, economic participation and overall well-being. Objectives: Determine PA levels of community-dwelling adults with traumatic spinal cord injury (TSCI) in the Cape Metropolitan, South Africa. Method: A quantitative, cross-sectional design was used in the Cape Metropole. The population included all community-dwelling adults with TSCIs, regardless of mobility status. Physical activity levels were measured using an ActiGraph wGT3X-BT accelerometer, classified by intensities: sedentary behaviour (SED), light intensity PA (LIPA) and moderate-to-vigorous PA (MVPA). Descriptive and analytical statistical tests described PA intensities and investigated group differences. Results: A total of 76 participants (mean age 36 years, standard deviation [s.d.] 10.93), mainly males (88.2%), were recruited. Time spent in SED, LIPA and MVPA among wheelchair users was 761.12 min/day (77.6%), 203.11 min/day (20.7%) and 16.96 min/day (1.7%), respectively. Ambulatory individuals spent 972.47 min/day (98.1%) in SED/LIPA and 18.80 min/day in MVPA (1.9%). Time since injury (p = 0.005) and age (p < 0.001) resulted in more MVPA for older wheelchair users and ambulatory individuals with recent injuries. Conclusion: Participants spend most time sedentary, followed by LIPA. Adults with SCI are not meeting recommended PA levels for health benefits. Understanding barriers to PA is essential for developing targeted interventions to optimise PA levels. Clinical implications: Cape Metropole's unique SCI profile with mostly young males, results in long-term injury impacts. Sedentary behaviour increases risks for morbidity and early mortality. Thus, exploring PA's role in SCI rehabilitation is important for healthy ageing.